Predictive immunohistochemical features for tumour response to chemoradiotherapy in rectal cancer. Issue 2 (5th February 2020) - Shinto, E.; Omata, J.; Sikina, A.; Sekizawa, A.; Kajiwara, Y.; Hayashi, K.; Hashiguchi, Y.; Hase, K.; Ueno, H.
Abstract : Background: Reduced expression of cluster of differentiation (CD) 133 and cyclo‐oxygenase (COX) 2, and increased density of CD8+ tumour‐infiltrating lymphocytes, are associated with a favourable tumour response to preoperative chemoradiotherapy (CRT). This study aimed to evaluate these markers in relation to tumour response after preoperative CRT in two rectal cancer cohorts. Methods: Patients with low rectal cancer who underwent radical resection and preoperative short‐term CRT in 2001–2007 (retrospective cohort) and long‐term CRT in 2011–2017 (prospective cohort) were analysed. Pretreatment biopsies were stained immunohistochemically using antibodies to determine CD133 and COX‐2 expression, and increased CD8+ density. Outcome measures were tumour regression grade (TRG), tumour downstaging and survival. Results: For 95 patients in the retrospective cohort, the incidence of TRG 3–4 was 67 per cent when two or three immunohistochemistry (IHC) features were present, but only 20 per cent when there were fewer features ( P < 0·001). The incidence of tumour downstaging was higher in patients with at least two IHC features (43 versus 22 per cent with fewer features; P = 0·029). The 49 patients in the prospective cohort had similar rates to those in the retrospective cohort (TRG 3–4: 76 per cent for two or more IHC features versus 25 per cent with fewer features, P < 0·001; tumour downstaging: 57 versus 25 per cent respectively, P = 0·022). Local recurrence‐free survival rates in patients with more or fewer IHC features were similar in the retrospective and prospective cohort ( P = 0·058 and P = 0·387 respectively). Conclusion: Assessment of CD133, COX‐2 and CD8 could be useful in predicting a good response to preoperative CRT in patients with lower rectal cancer undergoing neoadjuvant therapy. Further studies are needed to validate the results in larger cohorts and investigate a survival benefit. Abstract : The combination of reduced expression of cluster of differentiation (CD) 133 and cyclo‐oxygenase (COX) 2 and increased density of CD8+ tumour‐infiltrating lymphocytes is a significant predictor of tumour response to preoperative chemoradiotherapy (CRT). This finding may be clinically useful for determining chemoradiosensitive cancers. Immunoistochemistry features of tumor regression in rectal cancer Abstract : Antecedentes: La expresión reducida de CD133 and COX‐2, y un aumento en la densidad de los linfocitos infiltrantes del tumor CD8+ se han asociado recientemente con una respuesta favorable del tumor a la quimiorradioterapia preoperatoria ( preoperative chemoradiotherapy, CRT). Este estudio evaluó estos marcadores respecto a la respuesta del tumor tras CRT preoperatoria en dos cohortes de cáncer colorrectal. Métodos: Se analizaron pacientes con cáncer de recto bajo sometidos a resección radical y CRT preoperatoria de corta duración entre 2001–2007 (cohorte retrospectiva) y CRT de larga duración entre 2011–2017 (cohorte prospectiva). Se realizó tinción inmunohistoquímica ( immunohistochemical, IHC) con anticuerpos para CD133, COX‐2 y CD8 en las biopsias previas al tratamiento. Las características de interés incluyeron la disminución en las expresiones de CD133 y COX‐2, y la densidad aumentada de CD8+. Las variables de interés fueron los grados de regresión tumoral ( tumour regression grades, TRG) de acuerdo con Rödel, la reducción del estadio tumoral y las supervivencias. Resultados: La cohorte retrospectiva incluyó 95 pacientes. En este subgrupo, la incidencia de TRGs 3‐4 fue del 66, 7% en pacientes con dos o tres características de la IHC, mientras que solo fue del 20, 0% en pacientes con ninguna o con una característica ( P < 0, 001). Además, la incidencia de disminución del estadio tumoral fue más alta en pacientes que mostraban al menos dos características IHC (43, 3%) que en los controles (21, 5%; P = 0, 029). En la cohorte prospectiva se incluyeron 49 pacientes y la incidencia de estos hallazgos fue similar (TRG 3‐4, 76, 2% en ≥ 2 características IHC versus 25, 0% en los controles, P < 0, 001; disminución del estadio tumoral, 57, 1% en ≥ 2 características IHC versus 25, 0% en los controles, P = 0, 022). La supervivencia libre de recidiva local fue similar en las cohortes retrospectiva y prospectiva, cuando se compararon subgrupos de acuerdo con las características IHC ( P = 0, 058 y 0, 387, respectivamente) Conclusión: Este estudio sugiere que la evaluación de CD133, COX‐2 y CD8 podría ser útil para la predicción de una buena respuesta a la CRT preoperatoria en pacientes con cáncer de recto bajo sometidos a tratamiento neoadyuvante. Se necesitan estudios adicionales para validar los resultados en amplias cohortes e investigar el beneficio en la supervivencia.